Demand for quality vegetables in Malaysia - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Selamat, Jinap; Ramin, Abdul Ghariff (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
The objective of this study is to investigate the demand for quality vegetables in Malaysia. This study estimates quality elasticities from the difference between expenditure and quantity elasticities in order to show the demand for quality vegetables in Malaysia. By using the Household Expenditure Survey 2004/2005, expenditure and quantity Engel equations are estimated via two stage least square. The positive estimated quality elasticities (except root and tuberous vegetable) show that Malaysian consumers tend to increase their demand for quality vegetables in response to their incomes rise. To be more specific, urban consumers are expected to demand more of higher quality vegetables (except root and tuberous vegetable) than rural consumers.